2008
DOI: 10.1016/j.psychsport.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and achievement goals in athletes: Relations with approach and avoidance orientations in mastery and performance goals

Abstract: Objectives: Challenging views that perfectionism is a maladaptive factor in sport and that it is related to a preoccupation with performance goals and a neglect of mastery goals, the present article argues that perfectionism in athletes is not generally maladaptive, but shows differential relationships with mastery and performance goals depending on which facets of perfectionism are regarded. Method: Going beyond the dichotomous achievement goal framework, two studies with N = 204 high school athletes and N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 53 publications
9
67
1
8
Order By: Relevance
“…This view, however, disregards that perfectionism is multidimensional and that performance and mastery goals may follow two orientations: approach and avoidance. A recent study on multidimensional perfectionism and approach and avoidance orientations in mastery and performance goals (Stoeber et al, 2008, Study 2) found a distinct pattern of relationships between perfectionism and goals. Investigating student athletes and differentiating two facets of perfectionism-striving for perfection and negative reactions to imperfection-it was reported that striving for perfection was associated with mastery approach and performance approach goals, whereas negative reactions to imperfection were associated with mastery avoidance, performance approach, and performance avoidance goals.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…This view, however, disregards that perfectionism is multidimensional and that performance and mastery goals may follow two orientations: approach and avoidance. A recent study on multidimensional perfectionism and approach and avoidance orientations in mastery and performance goals (Stoeber et al, 2008, Study 2) found a distinct pattern of relationships between perfectionism and goals. Investigating student athletes and differentiating two facets of perfectionism-striving for perfection and negative reactions to imperfection-it was reported that striving for perfection was associated with mastery approach and performance approach goals, whereas negative reactions to imperfection were associated with mastery avoidance, performance approach, and performance avoidance goals.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, perfectionistic strivings and perfectionistic concerns are associated with different patterns of achievement goals, as was recently demonstrated in two studies with student athletes (Stoeber et al, 2008). Regarding perfectionism, two facets of perfectionism were examined (striving for perfection, negative reactions to imperfection), representing the dimensions of perfectionistic strivings and perfectionistic concerns, respectively.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This represents a problem because perfectionistic concerns-while not necessarily leading to impaired performance-have shown close links with characteristics and processes that may impair performance. Whereas perfectionistic strivings in athletes are associated with characteristics and processes that are likely to have positive effects on athletes' performance such as hope of success, competitive self-confidence, approach goal orientations, and self-serving attributions of success and failure (Stoeber & Becker, 2008;Stoeber, Stoll, Pescheck, & Otto, 2008), perfectionistic concerns in athletes are associated with characteristics and processes that are likely to have negative effects such as fear of failure, competitive anxiety, avoidance goal orientations, and self-depreciating attributions of success and failure (Sagar & Stoeber, 2009;Stoeber & Becker, 2008;. Moreover, perfectionistic concerns are associated with athlete burnout not only in adult athletes, but already in adolescent athletes (Gould, Udry, Tuffy, & Loehr, 1996;A.…”
Section: Implications For Applied Psychology [H1]mentioning
confidence: 99%
“…On the other hand, the performance-approach goal subscale assesses the emphasis placed on outperforming others in sport settings while the items comprising the performance-avoidance goal subscale are assumed to measure a concern with avoiding doing worse than others within the athletic milieu. At the present time, the AGQ-S is one of the most popular measures utilized in research centered on multiple achievement goals in sport (Conroy, Kaye, & Coatsworth, 2006;Conroy et al, 2003;Nien & Duda, 2008;Stoeber, Stoll, Pescheck, & Otto, 2008). In the case of a university recreational athlete sample from the US, the AGQ-S was found to have acceptable internal reliability and latent mean stability (Conroy et al, 2003).…”
mentioning
confidence: 95%